Lignolytic Enzyme Activity of Isolated Bacteria from Termite (Coptotermes Sp.) and Milkfish (Chanos chanos Forsskal, 1775) Guts - Emi Latifah; Putri Dwi Mulyani; Yekti Asih Purwestri (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2021)
Bacteria BSR 2, Pseudomonas alcaligenes (BSR 3), Brevibacillus parabrevis (BSR 8), Brevibacillus sp. (BSR 9), isolated from termite gut and Bacillus licheniformis (BSA B1) isolated from milkfish gut have been known to possess celluloytic activity. However, their lignolytic ability has not been known. This study aimed to determine the lignolytic ability of bacteria isolated from termit (Coptotermes sp.) and milkfish (Chanos chanos Forsskal, 1775) guts and their enzymes characterization. The qualitative test was done through the spot test method, while quantitative assay was performed spectrophotometrically at 335 nm to calculate vanillin concentration. The isolates were grown in Lignin Mineral Medium, then the optical density (OD620) were measured every 24 hours for 5 days using spectrophotometer to determine their growth profile and the best isolation time of the lignolytic enzyme. Based on results, the best lignolytic enzyme isolation time for strains Bacillus licheniformis (BSA B1) and BSR 2 were 5 days, yielding lignolytic enzyme activity of 0.961 ± 0.168 U/mg and 2.176 ± 0.088 U/mg respectively, while strains Pseudomonas alcaligenes (BSR 3), Brevibacillus parabrevis (BSR 8), and Brevibacillus sp. (BSR 9) were 4 days, yielding of 1.206 ± 0.045 U/mg, 1.162 ± 0.191 U/mg, and 0.896 ± 0.108 U/mg, respectively. The strain BSR 2 showed the highest lignolytic activity compared to other strains. The optimum temperature for lignolytic enzyme activity of BSR 2 was 30 ℃ and the optimum pH was 7. The lignolytic enzyme activity showed that these bacterial isolates can be a chance to be used as new alternative lignolytic enzyme source in commercial bioconversion process.